Maternal Fetal Trauma: When One Patient Becomes Two: A Case Study - Bonnie McCracken (Journal of Acute Care Surgery, 2020)
Trauma is a complication in an estimated 6-7% of pregnancies, and is the most frequent cause of obstetric death. Trauma has been shown to result in maternal or fetal death, and in cases of extensive trauma, both may die. Management of pregnant patients has multiple challenges. It requires coordination of the trauma and obstetrics teams, as well as other specialties specific to the injuries of the patient. Management of the pregnant female has been described in trauma literature, but there are few reports on the management of both mother and fetus, when both have sustained trauma injuries. This case study discusses the series of events when a mother and fetus have injuries, and the considerations required in the post-resuscitative period when both patients survive.